NILAI-NILAI KEPEMIMPINAN HINDU DALAM KITAB BISMA PARWA - Mardika, Made (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Hindu values or concepts of leadership can be found in the Veda scriptures, Arthasastra, Dharmasastra as well as in Itihasa books such as Ramayana and Mahabharata and Purana books such as the Agni Purana, Vayu Purana. In the Bhisma Parwa story, many leadership values are implied. The Bisma Parwa book contains very noble Hindu leadership values. These values are very good as a guide for Hindus in carrying out swadharma as a leader. Hindu leadership values contained in the Bisma Parwa Book include: Leadership Values Based on Principles (Dharma), Leadership Based on the Principles of Love (Prema) Leadership Based on Wise Principles (Vinayam). A good leader is he who can lead himself and others on the principle of dharmaYudhistira or truth.is the leader of the Pandavas and the king of Astina Pura. He leads with a strong and high love. A leader is not required to have an attitude of truth and love, but also be wise in carrying out government. This wise attitude can cause people to live in peace, peace and security. Yudhisthira's behavior as stated in Bhismaparwa as a leader embodies an attitude that is ahimsa or does not hurt. Therefore, never have aattitude himsa towards others. Especially people who are still in suffering.